The Role of Jam’iyyatul Islamiyah Organization in Strengthening Religious Moderation in Indonesia (Systems Theory Approach) - Waryani Fajar Riyanto (Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
This paper examines the role of the Jam'iyyatul Islamiyah (JmI) organization in strengthening the four religious moderation indicators that the government has formulated through the Ministry of Religious Affairs, namely: national commitment, tolerance, anti-violence, and adaptive to local customs or culture. Through a System Theory Approach, our study indicates that JmI has offered several strengthening factors such as the pillar of national commitment need to be strengthened by religious commitments; tolerance needs to be strengthened by i’tirafiyah insaniyah and ukhuwwah imaniyah; anti-violence with the innerfaith dialogue or innersubject dialogue; and adaptive to local culture with budi (the five senses) and morals or akhlak (reason, thought, illusion, understanding, knowledge). Moreover, the local customs need to be strengthened by syarak (innerspiritual or sunnah) and kitabullah (Qur’an). Finally, religious moderation (ummat wasath) will be a realization if there is an inclusion on the role of the innersubject (ruh) and God.